Cross-cutting effect of type 2 diabetes on the sensorimotor control of balance - Trevor Lopatin; Ben Borngesser; Joshua Haworth (Frontiers in Clinical Diabetes and Healthcare)
Type 2 Diabetes is a highly prevalent chronic disorder that affects multiple systems through microvascular complications. Complications such as diabetic peripheral neuropathy, diabetic retinopathy, and diabetic vestibular dysfunction (vestibulopathy) all directly interfere with the sensory components of balance and postural stability. The resulting impairments cause increased falls risk and instability, making it difficult to perform daily task or exercise. This commentary will provide clarity on the causes and relationship between the sensory complications of T2D, balance, and excise, while also providing recommendations and precautions for exercising with one of these sensory complications.